STRENGTHENING GLOBAL SUPPLY CHAIN RESILIENCE IN THE FACE OF CRISES AND EXTERNAL DISTURBANCES - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
Strengthening the resilience of global supply chains is a critical aspect in coping with increasingly complex and frequent external crises and disruptions, such as pandemics, climate change, and political instability. Companies are required to implement proactive strategies such as the use of advanced technology and good risk management to improve visibility and speed of response to disruptions. In addition, supplier diversification and increased operational flexibility are required to reduce dependence on single sources and enable rapid adaptation to changes. Effective collaboration and communication with all stakeholders is also a determining factor in improving supply chain resilience. The implementation of these strategies is expected to create a supply chain that is more resilient, adaptive, and able to face various external challenges.